THE EFFECT OF EGGPLANT JUICE TO THE THICKNESS OF AORTIC WALL IN WHITE RAT - Dwijayanti, ira (Widya Mandala Surabaya Catholic University, 2021)
Atherosclerosis is a complex chronic disease characterized by the accumulation of lipids within arterial walls. Delphinidin-3-(p-coumaroylrutinoside)-5-glucoside (nasunin), an anthocyanin, was isolated as purple-colored crystals from eggplant peels. Nasunin protection against induced lipid peroxidation in rat. The aim of study was to determine the effect of eggplant juice to the thickness of aortic wall of white rat with atherogenic diet. This true experimental laboratoric study using control group post test design performed in white rat that placed in pharmacologic laboratory of Brawijaya University. Sampling was carried out by completely random sampling with 25 rats for the total sample. Data were processed and analyzed using SPSS 16. Statistical test using one-way ANOVA and continuing with post hoc Tukey. The result showed there was a significant effect between positive control of diet atherogenic with the dosage I (1,3 gr/3 ml), dosage II (2,6 gr/3 ml), and dosage III (5,2 gr/3 ml) of eggplant juice to aorta wall thickness (p=0,000;p